Partial unilateral ovarian torsion in a red-eared slider turtle (Trachemys scripta elegans) - Vetere, Alessandro; Gavezzoli, Martina; Bel, Lucia Victoria; Di Lecce, Rosanna; Fumeo, Martina; Bonazzi, Mattia; Di Ianni, Francesco (Frontiers in Veterinary Science, 2025)
Follicular torsion occurs when only a group of ovarian follicles rotates around its own axis resulting in vascular compromise. To our knowledge, no previous reports have documented the occurrence of this condition in chelonians. A 14-year-old female Trachemys scripta was presented with inappetence and lethargy for approximately 2 weeks. Diagnostic tests, including complete blood work, radiography, and ultrasound, were performed. Radiographs showed no pathological changes, while blood tests showed mild heterophilia. Ultrasound revealed multiple, round, heterogeneous hyperechoic follicles and free anechoic fluid in the coelom. The color flow examination through the right pre-femoral fossa revealed the absence of blood flow in a group of follicles. A total body CT scan highlighted several rounded formations, four of which contained disomogeneus areas. Fluid with an air-fluid level and gas-filled areas were also noted in the coelomic cavity. A diagnosis of preovulatory follicular stasis and coelomitis was made, and a bilateral ovariosalpingectomy was performed endoscopically via the right prefemoral fossa after 24 h stabilization. There was a 360° torsion in a group of follicles, which appeared dark and had an increased consistency compared to adjacent follicles. Adhesions between the pathological follicles and surrounding tissue were observed. Bacteriological analysis of the coelomic fluid revealed the presence of Klebsiella spp. Histopathological examination of both ovaries showed coagulative necrosis, hemorrhage, congestion, and vascular thrombosis, along with a mixed inflammatory infiltrate. Post-surgical treatment with marbofloxacin and meloxicam resulted in significant clinical improvement. The animal was discharged 15 days after surgery, with a normal appetite.